2021
DOI: 10.3390/rs13193800
|View full text |Cite
|
Sign up to set email alerts
|

Fast and High-Quality 3-D Terahertz Super-Resolution Imaging Using Lightweight SR-CNN

Abstract: High-quality three-dimensional (3-D) radar imaging is one of the challenging problems in radar imaging enhancement. The existing sparsity regularizations are limited to the heavy computational burden and time-consuming iteration operation. Compared with the conventional sparsity regularizations, the super-resolution (SR) imaging methods based on convolution neural network (CNN) can promote imaging time and achieve more accuracy. However, they are confined to 2-D space and model training under small dataset is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The reconstruction of THz images based on deep learning for superior image quality through high and super resolution image reconstruction was also explored for; 3D THz image reconstruction [137], THz CT 3D image reconstruction [138]- [140] and 3D THz aperture radar imaging [141], [142]. THz coded aperture radar imaging.…”
Section: High and Super Resolution Thz Image Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reconstruction of THz images based on deep learning for superior image quality through high and super resolution image reconstruction was also explored for; 3D THz image reconstruction [137], THz CT 3D image reconstruction [138]- [140] and 3D THz aperture radar imaging [141], [142]. THz coded aperture radar imaging.…”
Section: High and Super Resolution Thz Image Reconstructionmentioning
confidence: 99%
“…The right-hand side of the architecture is the layout of the adaptive network (Na). The simulation and tested data acquired using a frequency modulated continuous wave (FMCW) real aperture scanner demonstrated effectiveness and superiority of their method quantitatively and qualitatively[136].The reconstruction of THz images based on deep learning for superior image quality through high and super resolution image reconstruction was also explored for; 3D THz image reconstruction[137], THz CT 3D image reconstruction[138]-[140] and 3D THz aperture radar imaging[141],[142]. THz coded aperture radar imaging.…”
mentioning
confidence: 99%
“…The developments in system-on-chip complementary metal oxide semiconductor (CMOS) radio frequency integrated circuits (RFIC) have resulted in the emergence of cost-effective frequency modulated continuous wave (FMCW) millimetre wave radars for imaging applications. The radar imaging systems include multiple input multiple output SAR (MIMO SAR), interferometric SAR (InSAR) and tomographic SAR [22]- [26]. In [8], a THz near-field imaging system based on SAR has been developed for precise, high resolution NDT of packaged aluminium etched antenna arrays and for flexible gold electrode array surface imaging.…”
Section: B Related Workmentioning
confidence: 99%
“…where 𝑤 and 𝑤 are the azimuth and range envelope respectively, 𝑇 is synthetic aperture time, 𝑓 is the range frequency variable, 𝐵 denotes the transmitted signal bandwidth and ∆𝑅 is the differential range. The full derivation of the PFA image reconstruction process has been derived in [22,23].…”
Section: G Polar Format Algorithmmentioning
confidence: 99%
“…Deeper networks can extract more information for picture reconstruction, but network overfitting makes training difficult. After that, Fan et al [ 21 ] proposed a lightweight SRCNN method to improve the image quality and to meet the demand of small datasets. In 2021, Su et al [ 22 ] suggested a novel subspace-and-attention-guided restoration network (SARNet), which adopted attention guidance to fuse spatio-spectral features of amplitude and phase.…”
Section: Introductionmentioning
confidence: 99%